(untitled) (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertension is a highly prevalent disease that has the potential to cause serious complications, while public awareness regarding its prevention and control remains low. Cupping therapy, as a complementary treatment, is believed to lower blood pressure through physiological mechanisms, making it a potential alternative in the sustainable management of hypertension. The purpose of this activity was to determine the effectiveness of cupping therapy among the residents of Sawapudo Village as a complementary method to reduce blood pressure in individuals with hypertension, by assessing changes in systolic and diastolic blood pressure before and after the intervention. The activity included blood pressure measurements and the administration of cupping therapy. Participants’ blood pressure was checked before cupping therapy and after the therapy, participants were checked again to see the difference. A total of 16 participants were involved, and initial assessments revealed that 7 individuals had high blood pressure (>120/80 mmHg), 5 experienced neck tension, and 4 complained of shoulder pain. Following these assessments, cupping therapy was carried out. The results showed that cupping therapy successfully reduced blood pressure (<120/80 mmHg), accompanied by a decrease in neck tension and shoulder pain. Therefore, cupping therapy is expected to serve as a complementary treatment for the community of Sawapudo Village in reducing blood pressure.